Pengaruh Terapi Reminiscence terhadap Penurunan Tingkat Kecemasan Lansia di Panti Sosial Tresna Werdha Inakaka Provinsi Maluku - Hitiayut, Mirdat; Hatuwe, Ernawati (Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the effect of reminiscence therapy on reducing anxiety levels in the elderly. This study used a quasi-experimental research design with a pretest and posttest nonequivalent control group. The sampling technique used total sampling to obtain 35 respondents. The research instrument used a questionnaire consisting of 14 questions and standard operating procedures for reminiscence therapy. The results of the paired sample t-test in the control group showed that there was no difference between anxiety levels in the pre-test and post-test. In the treatment group, there was a significant difference in reducing anxiety levels. The results of the study using an independent sample t-test showed that there was an effect of reminiscence therapy on reducing anxiety levels in the elderly at the Tresna Werdha Inakaka Social Home in Maluku Province.